1992
DOI: 10.1377/hlthaff.11.3.205
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Nation Perspective On The Elderly

Abstract: As the world faces the challenges of an increasingly aged population, this study examines the attitudes and experiences of those age sixty-five and older in five nations: the United States, Canada, the United Kingdom, western Germany, and Japan. Commissioned by the Commonwealth Fund Commission on Elderly People Living Alone and conducted by Louis Harris and Associates in 1991, the survey was undertaken to illuminate issues critical to the well-being of older people, including satisfaction with life, opportunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 1 publication
(1 reference statement)
2
7
0
6
Order By: Relevance
“…They work hard throughout their life and can then lead a comfortable, prosperous, and healthy life in their old age. 96 Mobile health information technology is spreading very rapidly and seems to be our future. Mobile devices can be taken by the elderly everywhere and used at any location.…”
Section: Discussionmentioning
confidence: 99%
“…They work hard throughout their life and can then lead a comfortable, prosperous, and healthy life in their old age. 96 Mobile health information technology is spreading very rapidly and seems to be our future. Mobile devices can be taken by the elderly everywhere and used at any location.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by sheer numbers, older persons may be more salient in social policies, common practices, and everyday discourse in Japan than in the U.S. With regard to living arrangements, older Americans are more likely than their Japanese counterparts to live alone: Over a decade ago, 31% of 65+ Americans lived alone, compared to 10% of older Japanese adults. Conversely, 32% of 65+ Japanese lived with children or others, while the counterpart figure for the U.S. was 15% (Rowland, 1992). More recent data indicated that in 2001, 58% of people 60+ lived with at least one of their children, which is 3 to 10 times greater than found in comparably developed Western societies such as the U.S. (17%), Germany (15%), and Sweden (5%) (Takagi, Silverstein, & Crimmins, 2007).…”
Section: Cultural Context and Well-being: The Need For A Life Course mentioning
confidence: 96%
“…É razoável supor que esses obstáculos apresentem-se com maior intensidade aos pacientes mais idosos, especialmente aqueles mais debilitados, portadores de condições de saúde que, em geral, requerem maiores gastos. Corrobora esta suposição uma pesquisa desenvolvida em cinco países que constatou que consultas a médicos no consultório, hospital ou telefone diminuem com a idade, aumentando as consultas no domicílio [21]. Análise de dados da Pesquisa Nacional por Amostra de Domicílios, realizada no Brasil em 1998, mostrou que a procura por atendimento médico entre homens e mulheres acima de 60 anos não aumentou com a idade [22].…”
Section: Tabela 4 -Freqüência E Distribuição Da Média Dos Gastos Do Munclassified